Concretização do direito à saúde no Brasil e na Índia: um estudo comparado - Bertotti, Bárbara Mendonça (Universidad Nacional del Litoral, 2021)
The purpose of this article is to compare the legal-constitutional regimes of Brazil and India regarding the realization of the right to health. To this end, first, general information about the two systems will be presented, notably on the aspects of the fundamental nature of this right, the constitutional guarantee, the ownership of the duty to ensure it, the participation of the private sector and public health systems (if any). Then, the chosen objects of study will be contrasted in order to identify their proximities. The comparative method will be used, based on the functionalist approach and the thought disseminated by Pierre Legrand. The conclusion is that the right to health has more excellent protection and normative density in Brazil, mainly because it is a constitutionally guaranteed fundamental right and because it has the Unified Health System as its public structure. In India, however, for not being constitutionally assured and not having a nationally structured public system, the right to health is at a lower level, and there is still much to be developed.